2017
DOI: 10.3389/fimmu.2017.01193
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms, Cofactors, and Augmenting Factors Involved in Anaphylaxis

Abstract: Anaphylaxis is an acute and life-threatening systemic reaction. Many triggers have been described, including food, drug, and hymenoptera allergens, which are the most frequently involved. The mechanisms described in anaphylactic reactions are complex and implicate a diversity of pathways. Some of these mechanisms may be key to the development of the anaphylactic reaction, while others may only modify its severity. Although specific IgE, mast cells, and basophils are considered the principal players in anaphyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
2
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 94 publications
5
56
2
6
Order By: Relevance
“…There may be temporal differences in severity from one allergen exposure event to another, possibly due to many factors (patient's clinical status, dose or type of allergen, cofactors, etc). In our study, around a quarter of anaphylaxis reactions had a cofactor which is quite similar to that previously reported …”
Section: Time Course Of Clinical Anaphylaxis Manifestations and Astiesupporting
confidence: 92%
“…There may be temporal differences in severity from one allergen exposure event to another, possibly due to many factors (patient's clinical status, dose or type of allergen, cofactors, etc). In our study, around a quarter of anaphylaxis reactions had a cofactor which is quite similar to that previously reported …”
Section: Time Course Of Clinical Anaphylaxis Manifestations and Astiesupporting
confidence: 92%
“…These latter symptoms may be treated with acetaminophen and monitored. Non‐steroidal anti‐inflammatory drugs should be avoided as they may serve as augmenting factors and worsen the reaction .…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that physical exercise, as well as the other facilitating factors, both increases the gastrointestinal absorption of food allergens and lowers the threshold for mastcell and basophil degranulation in sensitized individuals [48,49]. The great majority of patients with wheat-dependent exercise-induced anaphylaxis (WDEIA) have serum IgE specific for omega-5 gliadin and only in a minority of cases for high molecular weight glutenin (HMW-glutenin) [50].…”
Section: Clinical Presentation and Natural Historymentioning
confidence: 99%